Nonprofit Hospital Community Benefit in the U.S.: A Scoping Review From 2010 to 2019 - Rozier, Michael D. (Frontiers in Public Health, 2020)
Background: U.S. nonprofit hospital community benefit lately underwent significant regulatory revisions. Starting in 2009, the Internal Revenue Service (IRS) required hospitals to submit a new Schedule H that provided greater detail on community benefit activities. In addition, the Affordable Care Act (ACA), which became law in 2010, requires hospitals to conduct community health needs assessments (CHNA) and develop community health implementation plans (CHIP) as a response to priority needs every three years. These new requirements have led to greater transparency and accountability and this scoping review considers what has been learned about community benefit from 2010-2019. Methods: This review identified peer-reviewed literature published from 2010-2019 using three methods. First, an OvidSP MEDLINE search using terms suggested previously by community benefit researchers. Second, a PubMed search using keywords frequently found in community benefit literature. Third, a SCOPUS search of the most frequently cited articles in this topic area. Articles were then selected based on their relevance to the research question. Articles were organized into topic areas using a qualitative strategy similar to axial coding. Results: Literature appeared around several topic areas: governance; CHNA and CHIP process, content, and impact; community programs and their evaluation; spending patterns and spending influences; population health; and policy recommendations. The plurality of literature centered on spending and needs assessments, likely because they can draw upon publicly available data. The vast majority of articles in these areas use spending data from 2009-2012 and the first cycle of CHNAs in 2013. Policy recommendations focus on accountability for impact, enhancing collaboration, and incentivizing action in areas other than clinical care. Discussion: There are several areas of community benefit in need of further study. Longitudinal studies on needs assessments and spending patterns would help inform whether organizations have changed and improved operations over time. Governance, program evaluation, and collaboration are some of the consequential areas about which relatively little is known. Gaps in knowledge also exist related to the operational realities that drive community benefit activities. Shaping organizational action and public policy would benefit from additional research in these and other areas.